Green Business as a Moderating Variable for Financial Ratios and Firm Value - Chermian Eforis; Patricia Diana; Karina Harjanto (Conference Series, 2021)
According to the Environmental Performance Index (EPI), Indonesia is listed at 133, from 180 countries in the world. The Ministry of Environment and Forestry of the Republic Indonesia has established a company performance rating, namely, PROPER, whose assessment aspect is almost equal to EPI such as environmental permits, water and air pollution, and waste management. The purpose of this research is to see the effect of profitability, solvency, and liquidity toward firm value with PROPER rating as a moderation variable. Research was conducted over 45 companies in Indonesia from 2015-2019 using multiple regression analysis. The results showed profitability and solvency had positive significant effect on the firm value. Meanwhile, liquidity had negative significant effect towards firm value. PROPER rating positively moderates the effect of profitability and solvency on firm performance. However, it negatively moderates the effect of liquidity towards firm value.